Iyas anthology, 2001-2010. - Iyas National Writers' Workshop (Bacolod City University of St. La Salle, 2013)
A collection of poems and short stories selected the creative writing workshops organized by De La Salle University and University of St. La Salle in 10 years.
Poems and short stories.
In English, with some poems and short stories in Cebuano, Hiligaynon, and Filipino.
UCWS-2014-G-2128 donated by National Commission for Culutre & the Arts (NCCA)
Keywords: Short stories, Philippine; Philippine poetry; Philippine literature